2013
DOI: 10.3402/rlt.v21i0.18989
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with student response systems (SRS): teacher-centric aspects that can negatively affect students’ experience of using SRS

Abstract: In this article, we describe and discuss the most significant teacher-centric aspects of student response systems (SRS) that we have found to negatively affect students' experience of using SRS in lecture settings. By doing so, we hope to increase teachers' awareness of how they use SRS and how seemingly trivial choices or aspects when using SRS can have a significant negative impact on students' experiences, especially when these aspects are often repeated. We cover areas such as consistency when using SRS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
0
26
0
7
Order By: Relevance
“…The survey statements/questions presented in this paper are those related to classic versus peer instruction. For a description and discussions of other survey statements, see Nielsen, Hansen, and Stav (2013).…”
Section: Classicmentioning
confidence: 99%
“…The survey statements/questions presented in this paper are those related to classic versus peer instruction. For a description and discussions of other survey statements, see Nielsen, Hansen, and Stav (2013).…”
Section: Classicmentioning
confidence: 99%
“…This connection was described as 'close' and 'personal' suggesting a supportive relationship (Myers 2006); such supportive studentÁteacher relationships have been found to result in numerous positive benefits for student learning, satisfaction, motivation and retention. It must be noted that instructors need to learn, and indeed master, technology in the classroom so that time is not wasted in setting it up or managing it, so that it is used productively and not trivially and so that students remain interested in its use (Nielsen, Hansen, and Stav 2013). Nevertheless, large classes pose a barrier to the healthy development of positive studentÁinstructor relationships.…”
Section: Resultsmentioning
confidence: 99%
“…However, it can take some time to learn to use the new technology (Mareno et al, 2010). Nielsen et al (2013) found that lecturers with prior experience of ARS were rated higher by students. There appeared to be no need for special technical skills or training to be able to use the systems.…”
Section: Audience Response Systemsmentioning
confidence: 99%